Nurturing Self-Esteem in Early Childhood: A Novel Approach Through Parent-Teacher Collaboration in Positive Parenting - Heryanti, Yanti; Nurhayati, Sri (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2023)
Early childhood is a critical period for the development of self-esteem, which lays the foundation for future emotional and social well-being. In this context, the synergy between parents and teachers plays a pivotal role in influencing positive outcomes. This study aims to investigate the collaborative efforts of parents and teachers in implementing positive parenting to enhance self-esteem in early childhood. Utilizing a qualitative research method and approach, the study engaged in in-depth interviews and observations to collect data. The respondents included seven ECCE Principals and threeten parents who provided insights into their experiences and strategies in fostering positive parenting and self-esteem. Data analysis was conducted through thematic analysis, identifying patterns and themes related to parent-teacher collaboration. The findings reveal a significant emphasis on affection, mutual respect, and the development of warm relationships between children and parents. Furthermore, the study highlights the crucial role of open communication and shared values in aligning home and school environments to support children’s self-esteem. The implications of this research underscore the importance of a synergistic approach between parents and teachers, suggesting that such collaboration is vital for the optimal development of self-esteem in early childhood.